Generalized hereditary gingival fibromatosis in a child: clinical, histopathological and therapeutic aspects - John Lennon Silva Cunha; Maria Alice Carvalho da Cruz Ramos; Débora Menezes Regis; Celeste Sanchéz-Romero; Maria Eliane de Andrade; Bruno Torres Bezerra; Ricardo Luiz Cavalcanti de Albuquerque-Júnior (University of São Paulo, 2020)
Hereditary gingival fibromatosis (HGF) is a rare genetic condition characterized by slow and progressive gingival enlargement. The gingival overgrowth often delays teeth eruption and may cause serious functional and aesthetic problems. We reported a case of a 10-year-old female child presenting a generalized gingival enlargement covering almost all the maxillary and mandibular teeth and resulted in problems for swallowing, speaking, and poor aesthetics. An incisional biopsy was performed and revealed a hypocellular and hypovascular dense collagenous tissue covered by squamous epithelium exhibiting acanthosis and elongated rete ridges. The diagnosis was HGF. The treatment instituted was an association of gingivectomy with a rigorous program of oral hygiene and follow-up. Herein, we describe a rare non-syndromic case of generalized HGF, including clinical and microscopical features, as well as highlighting the importance of correct diagnosis of this genetic condition.